UAVs as Data Collectors in the WSNs: Investigating the Effects of Back-and-Forth and Spiral Coverage Paths in the Network Lifetime - Antunes, Jean Roberto; Brisolara, Lisane; Ferreira, Paulo (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2020)
Unmanned Aerial Vehicles (UAVs) have been applied to improve the lifetime of Wireless Sensor Networks (WSNs) in order to address problems like poor scalability and unbalanced energy consumption. This work compares two coverage path planning strategies, Spiral and Back-and-Forth (BF), in several relevant network setups. To evaluate the impact of adopting these UAV flight patterns, we ran experiments with three different relationships between communication and computation costs on the nodes, 25% communication per 75% CPU, 50% communication per 50% CPU, and 75% communication per 25% CPU. We aim to know what happens in different applications according to computational and communication requirements. For each relationship of cost, four different scenarios of network densities were evaluated, 49, 64, 81, and 100 nodes within the same area of interest. Our experimental results showed that UAV using Spiral path planning captured more events than the BF flight pattern, and BF captured more events and consumed less energy than a fixed sink WSN. Concerning network lifetime, the results of both path planning algorithms were very similar, but both overcame the standard fixed sink approach in all evaluated scenarios.